Caesarean section wound infections and antibiotic use: a retrospective case-series in a tertiary referral hospital in The Gambia. (July 2018) - Aulakh, Alex; Idoko, Patrick; Anderson, Suzanne T; Graham, Wendy
Ours is the first published study to examine post-Caesarean section (CS) wound infections in The Gambia. We explored risk factors and clinical management retrospectively at a large referral hospital over a 12-month period. A total of 777 cases were identified and records for 682 (88%) were retrieved. The CS rate was 21.8% and the wound infection rate 13.2%. Risk factors included: length of labour; decision-to-incision time and stillbirth. Only 7.4% of women received preoperative antibiotic prophylaxis, but all women received multiple-dose, postoperative antibiotics. The wound infection rate found is likely to be an underestimate owing to loss to follow-up. The adherence to international guidelines regarding preoperative antibiotic prophylaxis needs to be improved.